APPLICATION OF INTELLIGENT ANALYSIS IN TESTING THE DISTINCTIVENESS OF NEW ASPARAGUS VARIETIES (АSPARAGUS OFFICINALIS L.) - Leshchuk , Н.; Orlenko , Н.; Orlenko , О.; Dydiv , О.; Dydiv , І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The peculiarities of the formation of plant varietal resources of asparagus in Ukraine are analysed. The article investigates the varieties of asparagus included in the State Register of plant varieties suitable for distribution in Ukraine, evaluates these varieties with the allocation of groups of similar varieties of this botanical taxon; develops the elements of computer technology for intellectual data analysis using the machine learning method to simplify the process of analysing the uniqueness of a variety during the examination for distinctiveness, uniformity and stability (DUS) by classifying plant varieties according to their morphological characteristics. The results of the examination for distinctiveness, homogeneity and stability of asparagus were used for statistical processing. The modelling was carried out using the nearest neighbours algorithm, using the Machine Learning method in the IBM SPSS statistical package. A model of similar varieties of asparagus was formed. The model includes 11 varieties of asparagus, which are included in the State Register of Plant Varieties Suitable for Distribution in Ukraine. The model parameters were as follows: ‘Shoot emergence time’, “Shoot: anthocyanin colouration of the apex”, “Shoot: shape of the apex”, “Shoot: diameter at the base of the apex compared to the middle of the stem”, “Shoot: position of the cover leaves”, “Shoot: first cover leaf at the base of the apex in length”, “Shoot: first cover leaf at the base of the apex in width”, ’Plant: number of stems’, “Shoot: opening of cover leaves”, “Plant: density of phyllodes”, “Plant: intensity of green colour of leaves”, “Stem: length”, “Stem: length to first branching”, “Stem: diameter above soil surface”, “Flowering time”. The distances between the model parameters were calculated, which made it possible to identify the most similar and distinctive asparagus varieties. The target variable is “Plant: intensity of green colour of leaves”, the focus variable is “Stem: length”, and the label of observations is “Variety name”. The most similar groups of varieties were identified: “Bakhus” and “Erasmus”; “Guelph Eclipse” and “Guelph Millennium”. The most distinctive varieties are “Grolim”, “Baklim” and “Ginlim”. According to the indicators of economic and valuable characteristics of the varieties of asparagus, the highest yielding varieties were: “Signus”, “Kumulus”, “Bakhus” and “Erasmus”; the most resistant to root rot: “Bakhus”, “Guelph Equinox” and “Guelph Eclipse”, and against cercospora – varieties: “Signus”, “Kumulus”, “Prius”, “Bakhus”, “Erasmus” and “Guelph Equinox”.